(untitled) (Research, Society and Development, 2020)
The objective was to evaluate agronomically nine sorghum-sudangrass hybrids (Sorghum bicolor × Sorghum sudanense) and the nutritive value of their respective hays. The experimental design used was randomized blocks in a 3 × 9 factorial scheme, with three replications. Three cuts were made: 42 days after germination, 29 days after regrowth, and 28 days after the second regrowth. All hybrids showed a higher number of plants ha–1 (P < 0.05) in the second cut. For the green matter and dry matter production of the hays, the values ranged from 49.16 to 62.07 t ha–1 and 9.07 to 11.43 t ha–1, respectively. There were no differences (P > 0.05) in dry matter, mineral matter, or ether extract. The hybrids 1013020, BRS 810, 1013016, and 1624F016 showed higher values of crude protein (CP) of 16.49, 16.17, 16.08, and 15.88%, respectively. Differences were observed (P < 0.05) in neutral detergent fiber (NDF) content. The hybrids 1013020, BRS 802, 1013021, 1013016, BRS 810, and 1624F006 presented lower levels of NDF (60.57, 60.74, 62.15, 62.37, 62.58, and 64.70%, respectively). The hybrids BRS 802, 1013016, BRS 810, and 1624F006, stood out above the others, presenting high forage yield and adequate nutritive value (CP content >13% and NDF content <65%).